Thermoelectric spin transport through ferromagnetic heterostructures - Bender, Scott A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
We study how spin is transferred by ferromagnetic dynamics in a charge insulator in response to a thermoelectric bias, which is established by supplying heat and/or spin accumulation via normal leads. At zero temperature, magnetic anisotropies pin the macroscopic order, which necessitates a finite threshold bias to induce a spin current in a steady state of unpinned dynamics. At finite temperatures, however, thermal spin waves provide a spin transport channel in response to a linear thermoelectric bias. The theoretical description is rooted in the Landau–Lifshitz–Gilbert phenomenology both for the macroscopic dynamics of the magnetic order and quantum kinetics of thermal magnons. In this paper we connect the classical and quantum aspects of the underlying magnetic dynamics and spin transport, as well as provide a unified view of the exchange mediated bias of spin Seebeck physics of the magnetic interface and bulk.